Legal Protection For Outsourced Workers Who Are Dismissed Due To Disability Due To Work Accidents - Hermawan Hermawan; Rilawadi Rilawadi; Syariful Azmi (Legalpreneur Journal, 2022)
Workers / laborers can get work accident insurance if the employer or company has registered themselves and their workers as participants in the BPJS Ketenagakerjaan program. Based on the results of the study, the conclusion in this study is that the legal relationship between companies and workers based on Labor Law is the relationship between employers and workers/workers based on labor agreements, which have elements of work, wages, and orders and are regulated in Law Number 11 of 2020 concerning job creation. Based on Law Number 11 of 2020 concerning job creation Article 116, Article 117, Article 123 Article 124 and Article 151. One of the obligations of employers is to provide protection and safety for outsourced labor, especially for workers who have had work accidents who perform one job related to employment relations, in accordance with Article 151 Number 1 of the job creation Law Number 11 of 2020 stating employers or workers, unions/trade unions, and the government, with all efforts must try to avoid layoffs. Work accident that occurred in Sujatmiko resulting in defects in the hand, but as a result of the incident Sujatmiko laid off from his workplace, namely PT. PT. BIA without severance pay. Dinasker party gave a summons to PT. BIA. Then there was a bipartite meeting between Sujatmiko and PT. BIA accompanied by PT. KMP running Time 2 weeks finally PT. BIA issued severance pay of Rp.60,000,000 to Sujatmiko provided that the money given to PT. KMP to be channeled to Sujatmiko.